The Relationship between Maternal Vitamin D Deficiency and Low Birth Weight Neonates - Nasrin Khalessi; Majid Kalani; Mehdi Araghi; Zahra Farahani (Tehran University of Medical Sciences, 2015)
Objective:Maternal hypovitaminosis D may impair fetal growth and cause adverse pregnancy outcomes including intrauterine growth restriction and neonatal low birth weight. The aim of this study is to evaluate the relationship between maternal vitamin D status and neonate's birth weight. Materials and methods:A cross-sectional, descriptive analytical study was carried out in the nursery ward of 2 hospitals (Tehran-Iran) during one year (January 2011- January 2012). One hundred and two neonates were categorized into two groups, neonates with birth weight< 2500 gr (n=52) and neonates with birth weight>2500 gr (n=50). Data regarding medical history, physical examination and anthropometric measurements of neonates were noted in a questionnaire. Birth time blood samples of their mothers were analyzed for serum 25-(OH)-vitamin D by ELISA method. Maternal vitamin D status was compared in two groups. Results:Mean maternal vitamin D (vit D) level was 31.46 nmol/L. Forty eight percent of mothers had vitamin D deficiency, 27.5% had vit D insufficiency and 24.5% were normal. Mean maternal vitamin D level of LBW neonates was lower than other group; 25.05 vs. 38.13 (p= 0.001). All mothers of neonates with head circumference ≤ 33 cm also had vitamin D deficiency (p= 0.007). Conclusion:Maternal Vitamin Ddeficiency may increase the risk of low birth weight neonate and modifying maternal nutrition behavior and their vit D level could be beneficial on pregnancy outcome.